Human Resource Planning: Proposal for a New Journal - Walker, James W. (Academy of Management Journal, 1972)
A proposal is presented for a new journal titled “Human Resource Planning: A Quarterly Journal of Research and Practice.” The purpose of the new journal would be to promote effective human resource planning and related human resource management processes by publishing articles of noteworthy research and discussion. This journal would differ from other personnel management journals in that it is concerned with the planning and programming of human resource management actions with regard to corporate plans and objectives. Some of the aspects of the new journal that are outlined include subscription rate, the contents, the format, and the frequency of distribution.